SURVEI DAN PEMETAAN STATUS KALIUM LAHAN SAWAH PADA DAERAH IRIGASI BAHAL GAJAH/TIGA BOLON KECAMATAN SIDAMANIK - Wanaartha Nathalia Pardede; Supriadi Supriadi; Razali Razali (Jurnal Agroekoteknologi, 2013)
Survey and mapping potassium status on wet rice have been in irrigation area Bahal Gajah/TigaBolon in kecamatan Sidamanik. This research purpose to make a map potassium status on wet ricefield in irrigation area Bahal Gajah/Tiga Bolon. The research was started on April until December2012. Sampling method use free grid survey method with semi detail survey scale. Result ofanalysis process using correlation method, with Geographical Information System (GIS) program.Parameter that analysis in laboratory is exchange of potassium. The result of research showed thatpotassium exchange available devided by 5 status such as; lowest 0,118 ha (0,03%), low 1,542 ha(0,36%), medium 35,203 ha (8,24%), high 90,114ha (21,08%), and highest 300,473 ha (70,29%).Key words: mapping, potassium, paddy soil